Detection of 17β-Estradiol in Foods by a Fluorescence Aptasensor Based on Gold Nanoparticles - WEI Qingyi, LIN Xuanran, ZHANG Peiyao, SUN Da-wen, PU Hongbin (Shipin Kexue, 2023)
A fluorescent aptasensor was constructed for the high-sensitivity and high-selectivity detection of 17β-estradiol (E2) based on the fluorescence quenching effect of gold nanoparticles (AuNPs) on carbon quantum dots (CQDs) and the specific affinity of aptamers to targets. Under the optimal conditions (particle size of AuNPs = 39 nm, AuNPs amount = 200 μL, quenching time = 20 min, and fluorescence recovery time = 60 min), a good linear relationship was observed between the fluorescence recovery degree (y) of the sensor and the logarithmic value (x) of E2 concentration (2 × 10-5–2 × 10-9 mol/L), which was fitted with the following equation: y = 58.50x + 558.95 with a determination coefficient (R2) of 0.992. The detection of limit (LOD) of E2 was 3.4 × 10-10 mol/L. Finally, the aptasensor was successfully applied to the detection of E2 spiked in milk and environmental water samples with good recoveries of 89.67%‒113.36%, suggesting the potential for practical application.